Providing safe abortion services: Experiences and perspectives of providers in South Africa. (January 2020) - Harries, Jane; Constant, Deborah
Abstract: Despite abortion being legally available on request up to and including the gestational age of 12 weeks in South Africa, barriers to access remain. Barriers include provider opposition to abortion and a shortage of trained and willing providers, which has implications for access to safe abortion services. Exploring the factors that determine providers' levels of involvement in abortion services can facilitate improvements in service provision. Providers' conceptualizations of abortion are influenced by numerous factors, including moral and religious views, in which abortion is perceived by some as a sin, whereas others view access to safe abortions as an important component of a woman's right to reproductive autonomy and choice. Barriers to service provision include limited abortion and values clarification training and misinterpretation of conscientious objection. Providers have difficulties with the emotional and visual impact of second trimester abortions. There is an urgent need to address provider shortage, and abortion education and training need to be included in medical and nursing curricula to ensure sustaining abortion services. Highlights: Providers' perspectives key to improve safe abortion access in South Africa. Providers' religious and moral beliefs influence abortion provision. Interpretations of conscientious objection impact on abortion services. Repeat abortions and poor contraceptive uptake of concern to providers. Second trimester abortions are most challenging for providers.